2016
DOI: 10.3349/ymj.2016.57.2.430
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Analysis of Food Tolerance and Quality of Life after Laparoscopic Greater Curvature Plication

Abstract: PurposeThe aim of this study was to compare short-term outcomes [food tolerance scores (FTS) and quality of life] after three types of restrictive bariatric surgery: laparoscopic adjustable gastric banding (LAGB), laparoscopic greater curvature plication (LGCP), and laparoscopic sleeve gastrectomy (LSG).Materials and MethodsFrom January 2012 to December 2013, all patients that underwent primary surgery were included in one of the LAGB, LGCP, or LSG groups. These three groups were then compared with respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“… 5 7 On the other hand, LGCP has shown more sustained weight loss and higher levels of satisfaction Class I or II obese patients. 8 9 10 11 In another study, similar positive findings were reported for this patient population for LSG. 12 In the present study, we evaluated the treatment outcomes of LGCP and LSG in obese patients with a body mass index (BMI) ranging from 30 to 35 kg/m 2 .…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“… 5 7 On the other hand, LGCP has shown more sustained weight loss and higher levels of satisfaction Class I or II obese patients. 8 9 10 11 In another study, similar positive findings were reported for this patient population for LSG. 12 In the present study, we evaluated the treatment outcomes of LGCP and LSG in obese patients with a body mass index (BMI) ranging from 30 to 35 kg/m 2 .…”
Section: Introductionsupporting
confidence: 83%
“…However, the underlying mechanism of GERD appears to differ after LGCP or LSG. Kim and Kim 11 suggested that GER after LGCP is due to high intraluminal pressure and resulting ‘transient LES insufficiency’ rather than a damaged anti-reflux mechanism resulting from gastric resection during LSG. In our clinical experience, many patients complain of reflux symptom for several months after LGCP, but few complain of persistent symptomatic GERD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although gastric plication has functional restrictive effects [ 54 ], sleeve gastrectomy affects residual gastric volume, gastrointestinal tract motility, and hormonal balance [ 55 ]. The competence of gastric plication in weight loss has been demonstrated in clinical settings [ 56 , 57 ]. Comparative studies for LSG and LGP are not conclusive [ 26 , 29 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is widely known as a major health risk factor, and bariatric surgery has proved to be significantly effective and a safe procedure [ 8 ], results in sustainable and effective reduction in body weight [ 19 , 20 ], on a long-term basis [ 21 ], which provides meaningful weight loss and improvement in the quality of life [ 22 ], which is an effective alternative to the current standard procedures [ 23 ].…”
Section: Discussionmentioning
confidence: 99%